MORPHOLOGICAL VARIABILITY AND SEXUAL DIMORPHISM OF NOBLE CRAYFISH Astacus astacus FROM THE BALKANA LAKE - Roljić, Rajko; Nikolić, Vera; Savić, Nebojša (Bulletin of Natural Sciences Research, 2020)
This paper presents the information about morphological variability and sex dimorphism of the Noble crayfish (Astacus astacus) in the area of the Balkana Lake in Mrkonjic Grad. The crayfish were caught by hand made baited traps from October 9nd 2018. until May 31th 2019. A total of 58 crayfish were caught, of which 38 males and 20 females. The eight morphometric characteristics: body weight (W), body length (TBL), claw length (CLL), cephalothorax length (CFL), carapace width (CPW), abdomen length (ABL), rostrum length (ROL) and rostrum width (ROW) were measured, both in males and females. Also, the body condition was determined for all specimens. The results of morphometric characteristics partially matched into the already known range of variations. These data represent first ones for the observed area. The t-test showed that there were significant differences between the sexes in W, TBL, CLL, CFL and CPW which are explained by the emphasized sex dimorphism of the noble crayfish.